2013
DOI: 10.1111/nhs.12083
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a first‐aid intervention program applied by undergraduate nursing students to preparatory school children

Abstract: Childhood injuries constitute a major public health problem worldwide. First aid is an effective life-preservation tool at work, school, home, and in public locations. In this study, the effectiveness of a first-aid program delivered by undergraduate nursing students to preparatory school children was examined. This quasi-experimental study was carried out on 100 school children in governmental preparatory schools in Egypt. The researchers designed a program for first-aid training, and this was implemented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 25 publications
(28 reference statements)
1
23
0
3
Order By: Relevance
“…These results were in contrast with those of Lavanya, [22] in Bangalore, who reported that no association between knowledge about CPR among adolescents in selected schools and selected demographic variables like age, gender, grade, education and occupational level of parents. The study result was proved by two study results, the first one by Wafik and Tork, [6] in Zagazig City, Egypt, who stated that, a high number of parents of the study subjects are educated, which might have a positive impact on their children's knowledge. Thus, the correlation analysis showed a positive influence of parents' education on students' pre-intervention knowledge.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results were in contrast with those of Lavanya, [22] in Bangalore, who reported that no association between knowledge about CPR among adolescents in selected schools and selected demographic variables like age, gender, grade, education and occupational level of parents. The study result was proved by two study results, the first one by Wafik and Tork, [6] in Zagazig City, Egypt, who stated that, a high number of parents of the study subjects are educated, which might have a positive impact on their children's knowledge. Thus, the correlation analysis showed a positive influence of parents' education on students' pre-intervention knowledge.…”
Section: Discussionmentioning
confidence: 90%
“…[5] School children are highly exposed to emergency situations because mental and physical abilities of children are not developed enough to allow them to protect themselves; they sustain accidents and injuries frequently, in addition of increasing activity, tendency of children to involve into dangerous physical behavior and persistent violent act. [6] The students, acquisition and reinforcement of basic emergency life saving skills training during the school ages may enhance students confidence to respond to an emergency condition and may provide updating for these skills after high school graduation. [4,7] Health education to school children is the most effective way for protection and promotion of their health.…”
Section: Introductionmentioning
confidence: 99%
“…5(2), 2543-2551 2544 provide first aid because they feared to carry out something in the wrong way (1). Numerous studies have revealed a clear association between the level of first aid education and the excellence of first aid measures and actions provided (2,3). This emphasizes the value of first aid training for the public.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…This emphasizes the value of first aid training for the public. It is well-known that the school location can be one of the most common locations to witness an emergency (2), Early and appropriate management of such emergencies and injuries can reduce complications and mortality (4). Appropriately administered first aid indicates the discrepancy between life and death, quick versus delayed recovery and short-term versus long term disability (5) so this study was conducted on the grounds of evaluating the outcomes of giving a first-aid course to secondary school students 16 -18 years old as they are a part of an age group that represent the majority of our population.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
See 1 more Smart Citation